BIMBINGAN TEKNIS PROSES PRODUK DAN SERTIFIKASI HALAL BAGI PELAKU USAHA PANGAN MIKRO KECIL DI DESA NAPALAKURA KABUPATEN MUNA - Faradilla, RH. Fitri; Leomo, Sitti; Saediman, H; Rejeki, Sri (HIRONO : Jurnal Pengabdian Masyarakat, 2023)
Napalakura Village is a village that is famous for its processed fish products, such as shredded fish, fish sauce, and frozen fishery products. These products have high selling power and have the potential to be marketed outside the island of Muna. However, most of the food products produced in Napalakura Village and its surroundings are still not halal certified. For this reason, technical guidance on the product process and halal certification is carried out with the aim that these products are guaranteed halal and do not experience obstacles to be marketed. This training is carried out with a series of activities consisting of (a) counseling on halal materials and production processes; (b) assistance in the process of making halal certificates. The results of this training are a) increasing knowledge about halal materials and production processes; b) the food products produced are certified. The results of this training evaluation show that there has been an increase in knowledge and the issuance of halal certificates from technical guidance participants.